Implementation of entrepreneurship management principles in addressing challenges of startup businesses - Irham Fahmi; Jalaluddin Jalaluddin; Zulfadli Zulfadli (Jurnal Mantik, 2023)
The main objective of this study is to investigate how Entrepreneurship Management Principles can assist startups in overcoming their challenges. It focuses on how these principles enhance startup competitiveness, innovation, and adaptability in dynamic markets. The research employs a systematic literature review approach, conducting a comprehensive search in databases like Scopus, Google Scholar, and Web of Science using relevant keywords. Inclusion criteria involve articles published between 2015 and 2023, written in English, and categorized as research articles in international publications. Quality assessment tools like the Critical Appraisal Skills Programme (CASP) were utilized to ensure article credibility. The findings from the literature review highlight the vital role of Entrepreneurship Management Principles in startup success and growth. Startups that apply these principles demonstrate increased innovation, efficient resource management, and effective adaptation to market changes, enhancing their competitiveness and sustainability. A supportive work environment promoting creativity and innovation is also crucial for startup success. This study contributes to our understanding of the significance of Entrepreneurship Management Principles in addressing startup challenges, offering practical insights for entrepreneurs, policymakers, and business leaders to create a conducive ecosystem for startup growth. Embracing these principles can empower startups to seize opportunities, stand out from competitors, and achieve long-term success in a competitive business landscape